A importância do registro para a reflexão crítica da prática no chão da escola de Educação Infantil - Romero, Tais (2020)
This research has the general objective of investigating the role of reflective record in the development of the planning in the Early Childhood Education. From the general objective, the following specific objectives are unfold: to look into the education training potential of reflective planning in the Early Childhood Education; to understand who trains who in the process of continuing education of Early Childhood Education teachers; to outline the role of continuing education training as a reflective process for Early Childhood Education. The research focus, therefore, is the record as a critical reflection for the consolidation of Education training actions in Early Childhood Education. The theoretical-methodological framework adopted was based on the principles of action research (EBBUTT; ELLIOT, 1990; THIOLLENT, 2011; TRIPP, 2005) and in studies about the continuing education of teachers in service (ALMEIDA, 2015; BENACHIO; PLACCO, 2012; FREIRE, 2011), about the reflective record (HOYUELOS; RIERA, 2019; ZABALZA, 2004) and about reflective planning (HOYUELOS; RIERA, 2019). Three teachers of Early Childhood Education, from a private school located in São Paulo (state of São Paulo), participated in this study, based on the advisory work provided by the researcher, for the period of one year. The research data source was the records produced by the participants during that period, which were sent to the researcher by WhatsApp message and e-mail. The data analysis was developed according to an authorial methodology, which accompanied the records´ transformation along the work. The results show that these records started from a writing production with a primarily bureaucratic character and were being transformed, throughout the advisory work, into a reflective writing. In this regard, it is understood that the reflective record can be used as a tool with a potential to transform the planning carried out by the teachers and, the teaching work as a whole, as long as it leaves aside its bureaucratic character and starts to serve the teacher in the critical reflection on the practices. Thus, the need for change and transformation is considered, emphasizing the record, which is an instrument of reflection on one's own practice, with the potential to reframe the teaching profession, facing a society that attributes to the teacher the role of merely theories transmitter, which have been reproduced throughout its trajectory, as learners (“aprendente”) and as teachers (“ensinante”)